Dampak Kemampuan dan Pengalaman Kerja terhadap Kinerja Karyawan - Ahmad Sumitra; Deni Muhammad Danial; Eryy Sunarya (Journal of Management and Bussines (JOMB), 2019)
This study aims to determine the effect of Ability (Variable X1) and Work Experience (Variable X2) on employee performance. The method used in this study is using descriptive methods and associative methods. Data collection techniques conducted by researchers in this study are through observation, questionnaire interviews, documentation and literature study. Data analysis techniques start from the compilation of data, tabulation of data up to the testing phase. Based on the results of the calculation of the study of multiple linear regression analysis. The coefficient of determination (R2) can be obtained from the capability variable (X1) and work experience (X2) affects 89.8% (0.898) on employee performance (Y), the remaining 10.2% is influenced by other factors outside the research this. Conclusions, abilities and work experience have an impact on employee performance Keywords: Ability, Work Experience, Employee Performance.